Skills and abilities to thrive in remote work: What have we learned - Henke, Jonn B.; Jones, Samantha K.; O’Neill, Thomas A. (Frontiers in Psychology, 2022)
The COVID-19 pandemic led to a rapid acceleration in the number of individuals engaging in remote work. This presented an opportunity to study individuals that were not voluntarily working remotely pre-pandemic and examine how they adapted and learned to achieve success in a remote work environment, at an organization that did not have substantial prior experience managing remote work. We used a semi-structured interview process to interview participants (n = 59) who occupied both Individual Contributor and Leadership levels at an organization and broadly representative across several important demographic characteristics. We asked participants to discuss what factors at individual, team, and organizational levels contributed positively towards their remote work experience, which factors presented challenges to remote work, and what could be done to ensure success with remote work in the future. Interviews were analyzed utilizing a thematic analysis approach and summarized into common themes pertaining to factors that influence success in a remote working environment. Themes were used to identify specific skillsets particularly relevant to remote work that would benefit from training, as well as important organizational culture changes and policies needed to support remote workers and ensure their success. We present these and other findings in relation to current research and provide recommendations for practitioners.